Performance-based financing at the Global Fund to Fight AIDS, Tuberculosis and Malaria: an analysis of grant ratings and funding, 2003-12 - Victoria Y Fan, ScD; Denizhan Duran, BA; Rachel Silverman, BA; Amanda Glassman, MSc (Elsevier, 2013)
Background: Performance-based financing can be used by global health funding agencies to improve programme performance and thus value for money. The Global Fund to Fight AIDS, Tuberculosis and Malaria was one of the first global-health funders to deploy a performance-based financing system. However, its complex, multistep system for calculating and paying on grant ratings has several components that are subjective and discretionary. We aimed to test the association between grant ratings and disbursements, an indication of the extent to which incentives for performance are transmitted to grant recipients. Methods: We obtained publicly available data for 508 Global Fund grants from 2003 to 2012 with performance ratings and corresponding disbursements, merged with other datasets that contained data for relevant country characteristics. We used regression analysis to identify predictors of grant disbursements in phase 2 (typically the latter 3 of 5 years of a grant), using two dependent variables: whether a grant had any phase-2 disbursements, and the phase-2 disbursement amount. In a separate analysis, we also investigated the predictors of grant performance ratings. Findings: Grant performance rating in phase 1 was positively associated with having any disbursements in phase 2, but no association was seen between phase-1 ratings and phase-2 disbursement amounts. Furthermore, performance ratings are not replicable by external observers, both because subjective and discretionary decisions are made in the generation of performance measures and because the underlying data are not available. Interpretation: The Global Fund's present performance-based funding system does not adequately convey incentives for performance to recipients, and the organisation should redesign this system to explicitly link a portion of the funds to a simple performance measure in health coverage or outcomes, measured independently and robustly. Funding: Bill & Melinda Gates Foundation.